RETRACTED: Berberine Maintains the Neutrophil N1 Phenotype to Reverse Cancer Cell Resistance to Doxorubicin - Zhang, Shuhui; Zhou, Lin; Zhang, Mengdi; Wang, Yuehua; Wang, Mengqi; Du, Jincheng; Gu, Wenwen; Kui, Fuguang; Li, Jiahuan; Geng, Shengnan; Du, Gangjun (Frontiers in Pharmacology, 2020)
This study explores the contributions of neutrophils to chemotherapeutic resistance and berberine-regulated cancer cell sensitivity to doxorubicin (DOX). In vitro experiments, continuous DOX treatment led to the shift of HL-60 cells to N2 neutrophils and thus induced chemotherapeutic resistance. The combination treatment with DOX and 2 µM berberine resulted in the differentiation of HL-60 cells towards N1 and therefore stimulated HL-60 cell immune clearance. Berberine increased reactive oxygen species (ROS) and decreased autophagy and therefore induced apoptosis in HL-60-N2 cells with morphological changes, but had no effect on cell viability in HL-60-N1 cells. The neutrophil-regulating efficacy of berberine was confirmed in the urethane-induced lung carcinogenic model and H22 liver cancer allograft model. Furthermore, we found that DOX-derived neutrophils had high levels of CD133 and CD309 surface expression, which prevented both chemotherapeutic sensitivity and immune rejection by self-expression of PD-L1 and surface expression of PD-1 receptor on T cells, whereas berberine could downregulate CD133 and CD309 surface expression. Finally, berberine-relevant targets and pathways were evaluated. This study first suggests an important role of berberine in regulating neutrophil phenotypes to maintain cancer cell sensitivity to DOX.